Gut Microbiota Metabolite Fights Against Dietary Polysorbate 80-Aggravated Radiation Enteritis - Li, Yuan; Xiao, Huiwen; Dong, Jiali; Luo, Dan; Wang, Haichao; Zhang, Shuqin; Zhu, Tong; Zhu, Changchun; Cui, Ming; Fan, Saijun (Frontiers in Microbiology, 2020)
Radiation therapy is a cornerstone of modern management methods for malignancies but is accompanied by diverse side effects. In the present study, we showed that food additives such as polysorbate 80 (P80) exacerbate irradiation-induced gastrointestinal (GI) tract toxicity. A 16S ribosomal RNA high-throughput sequencing analysis indicated that P80 consumption altered the abundance and composition of the gut microbiota, leading to severe radiation-induced GI tract injury. Mice harboring fecal microbes from P80-treated mice were highly susceptible to irradiation, and antibiotics-challenged mice also represented more sensitive to radiation following P80 treatment. Importantly, butyrate, a major metabolite of enteric microbial fermentation of dietary fibers, exhibited beneficial effects against P80 consumption-aggravated intestinal toxicity via the activation of G-protein-coupled receptors (GPCRs) and maintenance of the intestinal bacterial composition in irradiated animals. Moreover, butyrate had broad therapeutic effects on common radiation-induced injury. Collectively, our findings demonstrate that P80 are potential risk factors for cancer patients during radiotherapy and indicate that butyrate might be employed as a therapeutic option to mitigate the complications associated with radiotherapy.